Fish abundance is enhanced within a network of artificial reefs in a large estuary - Grimes, Charlotte E.; Morley, James W.; Richie, Diandre′ N.; McMains, Andrew R. (Frontiers in Marine Science, 2024)
Artificial reefs may be created within estuaries for multiple reasons, including habitat enhancement, oyster production, or recreational fishing. While traditional sampling in this environment is difficult due to complex structures and the high turbidity of estuaries, acoustic imaging sonar provides an effective alternative to measure abundance and size spectra of the fish community. We sampled eight artificial reefs in Pamlico Sound, North Carolina, that are designated as oyster sanctuaries. At each oyster sanctuary, we sampled 26 boat positions along two transects using ARIS imaging sonar, which included control areas outside of the sanctuaries over featureless bottom. We found that fish abundance and mean length were greater within the oyster sanctuary boundaries, but did not observe any significant differences among artificial substrate types within the sanctuaries. Further, we found that fish abundance dropped to near background levels within 25 m outside of the oyster sanctuary edge. Size spectra analysis revealed that abundance was higher in the sanctuaries versus control areas for every length bin of the fish community (5 to 50 cm). However, the differences in abundance were greatest for 10 to 30 cm fishes. Our results can be coupled with previous research on species composition data to more fully understand the potential role that the Pamlico Sound oyster sanctuaries, and estuarine artificial reefs in general, serve as habitat and recreational fishing enhancement.